Exploring and Explaining Regional Variability in Attitudes toward China-Pakistan Economic Corridor (CPEC) - Muhammad Shahid; Muhammad Javed; Muhammad Sajid; Azhar Ali Abbas (Indus Journal of Social Sciences, 2025)
The objective of this paper is to examine stakeholders' attitudes toward the China-Pakistan Economic Corridor (CPEC), a highly contested at a point project promoted by China as a part of the Belt and Road Initiative implementation. To evaluate the attitudes quantitative (online questionnaire survey and subsequent analysis) methods were employed. The findings show that over time the initially negative attitudes toward the CPEC subsided, while regional variability in attitudes exists. For instance, respondents from the Gilgit Baltistan province showed more interested in CPEC, while respondents from the Baluchistan province showed a lack of interest in CPEC. The really interesting question is which factors explain these regional differences in attitudes. To this end, the lack of education and political instability are explored as countervailing factors. The value added of this paper consists in its conceptual and empirical implications, e.g. on the one hand, the study provides a conceptual framework of analysis that can be applied to evaluate other groups of stakeholders and their attitudes toward CPEC. On the other hand, the insight into regional differentiation and the factors underlying it may serve as a background of policy planning and strategy building to be employed by decision-makers.